Efektivitas Penerapan Qanun Jinayah di Nangroe Aceh Darussalam Ditinjau dari teori Social Engineering Roscoe Pound - Ernida Septiani; Elsya Nopiani; Bintang Bhakti Alamsyah; Aldi Bahtiar; Deden Najmudin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2026)
This study analyzes the effectiveness of the Qanun Jinayah in Aceh as an instrument of social engineering through the lens of Roscoe Pound's Social Engineering Theory. Employing a qualitative library research method, the findings indicate that while the Qanun is designed as a tool to shape a homogeneous religious society, its implementation faces complex challenges. From Pound's perspective, effective law must balance various interests. However, in practice, the Qanun Jinayah tends to prioritize collective interests in the name of religious morality while overlooking individual interests, such as the right to privacy and protection from degrading punishment, and demonstrates a vulnerability to gender bias. The repressive legal approach, manifested through public caning, has proven more successful in creating temporary, instrumental compliance rather than fostering internal and sustainable value change within society, as evidenced by the phenomenon of violations shifting to private spaces. Further challenges, such as inconsistent enforcement across regions and polarized public attitudes, erode the Qanun's social legitimacy. This research concludes that the Qanun Jinayah has not been fully effective as a social engineering tool. Its revolutionary and legalistic approach is potentially counterproductive, risks reducing religious spirituality to formal compliance, and can undermine social solidarity. A more comprehensive strategy is required for successful social engineering, one that moves beyond punitive measures to build legal consciousness through inclusive public education and dialogue, thereby creating a more equitable balance of interests